The strengthening relationship between economy and government spending: the case of Indonesia - Hasdi Aimon; Agus Irianto; Yeniwati Yeniwati (Proceedings of AICS - Social Sciences, 2017)
This study explains the Indonesian economy recently experienced a weakening or slowing in the first quarter of 2015 that showed economic growth of 4.7 percent. It is certainly believed to be caused by internal and external factors, which impacted on the Indonesian government spending either in 2015 or in 2016. This study uses time series data. Furthermore, stationary and cointegration tests were analyzed using multilevel regression model with Ordinary Least Square (OLS) and an Error Correction Mechanism (ECM) model. The results of this study will determine the internal and external factors that strengthen or weaken the relationship between the economy and government spending in Indonesia. Thus, based on these findings, policy in overcoming economic difficulties can be determined and local and central government budget for 2016 can be established.